1991
DOI: 10.1007/bf03036956
|View full text |Cite
|
Sign up to set email alerts
|

Local cerebral blood flow with prostaglandin E1 or trimethaphan during cerebral aneurysm clip ligation

Abstract: This study was performed to examine changes in local cerebral blood flow during hypotensive anaesthesia with either prostaglandin E1 (PGE1) or trimethaphan (TMP). Local cerebral blood flow (LCBF), mean blood pressure (MBP), heart rate (HR ), and hourly urine output (UO) were studied in 51 patientsDeliberate hypotension is frequently employed to decrease blood loss during surgery and to diminish the need for and the risk of blood transfusion. L2 The characteristics of an ideal hypotensive drug include easy admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4 In previous studies, we reported that prostaglandin E I (PGE 0 mainmined local cerebral blood flow (LCBF) and carbon dioxide reactivity, 5 and that trimethaphan decreased cerebral blood flow during cerebral aneurysm surgery. 6 The purpose of this study was to compare the effects of PGE 1 or nitroglycerine (TNG) on carbon dioxide reactivity and local cerebral blood flow during isoflurane anaesthesia.…”
mentioning
confidence: 99%
“…4 In previous studies, we reported that prostaglandin E I (PGE 0 mainmined local cerebral blood flow (LCBF) and carbon dioxide reactivity, 5 and that trimethaphan decreased cerebral blood flow during cerebral aneurysm surgery. 6 The purpose of this study was to compare the effects of PGE 1 or nitroglycerine (TNG) on carbon dioxide reactivity and local cerebral blood flow during isoflurane anaesthesia.…”
mentioning
confidence: 99%
“…It is important that cerebral blood flow is maintained during induced hypotension. There are also discrepancies about the effect of PGE 1 on cerebral blood flow as previously mentioned: increase (9), no change (1, 11), or decrease (10). Although we did not measure cerebral blood flow, pial artery dilated during severe hypotension with the highest dose of PGE 1 .…”
Section: Discussionmentioning
confidence: 91%
“…I NTRAVENOUS prostaglandin E 1 (PGE 1 ) is reported to be safe and useful for controlled hypotension during surgery (1). Its main advantages include a rapid onset of action, a quick recovery from hypotension (2) due to a short elimination half‐life, lack of toxicity, maintenance of adequate perfusion to vital organs (1, 3), and maintenance of cerebral blood flow reactivity to carbon dioxide (4, 5) during hypotension. The elimination half‐lives of PGE 1 are reported to be 0.2 min (alpha phase) and 8.2 min (β phase) (6).…”
mentioning
confidence: 99%
“…In spite of its hypotensive effect, cerebral, coronary, and renal blood flows are maintained with the use of PGE 1 . 22,23 We determined the dosage of PGE 1 according to previous reports. At the dosage of 100 ng·kg -1 ·min -1 , PGE 1 reduces blood pressure by relaxing the vascular smooth muscle.…”
mentioning
confidence: 99%